Analisis Core Recovery Menggunakan Metode TCR dan Faktor Pengaruhnya pada Sampel Pengeboran Emas di PT Pegasus Mineral Nusantara, Aceh Tengah - Zabal Nur; Anarta, Rudy; Anaperta, Yoszi Mingsi (Yayasan Literasi Sains Indonesia, 2025)
Exploration is a crucial stage in mining activities, providing quantitative and qualitative information about the existence of mineral deposits. One direct exploration method used is core drilling, which involves retrieving subsurface rock samples (cores) for laboratory analysis. The results of these analyses serve as a fundamental database for resource estimation. One key parameter for evaluating the success of core drilling is the core recovery value, which is the ratio of the length of the core obtained to the total length drilled. This value reflects how well the core represents actual subsurface geological conditions. PT Pegasus Mineral Nusantara is currently conducting core drilling activities as part of a gold exploration project located in Paya Tampu Village, Rusip Antara District, Central Aceh Regency, Aceh Province. However, several issues have been encountered during core drilling, such as core loss due to falling back into the borehole and discrepancies in measured core lengths (gain/loss). This study aims to calculate and analyze core recovery using the Total Core recovery (TCR) method from drilling samples and identify the factors affecting core recovery success. The findings of this research are expected to contribute to improving the quality and reliability of mineral exploration drilling programs.